The Picky Eagle : How Democracy and Xenophobia Limited U.S. Territorial Expansion - Maass, Richard W. (Book collections on Project MUSE., 2020)
"This book explains why the United States stopped annexing territory by focusing on annexation's domestic political and normative consequences"--